Impurity transport studies at Wendelstein 7-X by means of x-ray imaging spectrometer measurements*Invited paper published as part of the Proceedings of the 45th Conference on Plasma Physics (EPS), Prague, Czech Republic, July, 2018. (23rd November 2018) - Langenberg, A; Warmer, F; Fuchert, G; Marchuk, O; Dinklage, A; Wegner, Th; Alonso, J A; Bozhenkov, S; Brunner, K J; Burhenn, R; Buttenschön, B; Drews, P; et al.
Abstract: This paper reports on the effect of on- and off-axis heating power deposition on the impurity confinement in purely electron cyclotron resonance heated He plasmas on the stellarator Wendelstein 7-X. Therefore, impurity transport times τ I have been determined after Fe impurity injections by laser ablations and monitoring the temporal impurity emissivities by the x-ray imaging spectrometer HR-XIS. A significant increase of τ I has been observed when changing the power deposition from on- to off-axis heating with energy confinement times τ E being mainly unaffected. In addition, the scaling of impurity transport properties with respect to a variation of heating power P ECRH and electron density n e has been investigated by keeping the heating power deposition on-axis. The observed τ I scaling compares well to known τ I scaling laws observed in other machines. A comparison of τ I and τ E yields an averaged ratio of τ E / τ I  = 1.3 and transport times in the range of τ I  = 40–130 ms and τ E  = 40–190 ms. Comparing those absolute values to neoclassical predictions supports the recently observed nature of anomalous transport in Wendelstein 7-X, given within the up to now investigated operational parameters.